A Randomized Trial of Behavioral Physical Therapy Interventions for Acute and Sub-Acute Low Back Pain (NCT00373867) - George, Steven Z. (2008)
Psychological factors consistent with fear-avoidance models are associated with the development of chronic low back pain (LBP). As a result, graded activity (GA) and graded exposure (GX) have been suggested as behavioral treatment options. This clinical trial compared the effectiveness of treatment based classification (TBC) physical therapy alone, to TBC augmented with GA or GX for patients with acute and sub-acute LBP. Our primary hypothesis was that GX would be most effective for those with elevated pain-related fear. In total, 108 patients enrolled in this clinical trial and were randomly assigned to receive TBC, GA, or GX. Outcomes were assessed by a blinded evaluator at 4-weeks and by mail at 6-months. The primary outcomes for this trial were disability and pain intensity, and secondary outcomes were fear-avoidance beliefs, pain catastrophizing, and physical impairment. There were no differences in 4-week and 6-month outcomes for reduction of disability, pain intensity, pain catastrophizing, and physical impairment. GX and TBC were associated with larger reductions in fear-avoidance beliefs at 6-months only. Six month reduction in disability was associated with reduction in pain intensity, while 6-month reduction in pain intensity was associated with reductions in fear-avoidance beliefs and pain catastrophizing. This trial suggests that supplementing TBC with GA or GX was not effective for improving important outcomes related to the development of chronic LBP.